1994
DOI: 10.1039/c39940000681
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation in water solutions of tetrasodium diprotonated meso-tetrakis(4-sulfonatophenyl)porphyrin

Abstract: The title porphyrin shows non ideal cmc with formation of J-aggregates, due to the formation of intermolecularly stabilized zwitterions, which at high concentration also results in H-aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
250
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(264 citation statements)
references
References 17 publications
11
250
2
1
Order By: Relevance
“…An optical and topographic resolution of about 100 and 160 nm, respectively, with an optical contrast C ) 18% is derived. sulfonatophenyl)porphine (TPPS), [24][25][26][27][28] which under strong acidic conditions form extended J-aggregates. Several investigators have pointed out that coplanarity is a prerequisite for the initial dimerization step, together with the presence of negatively charged groups on the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…An optical and topographic resolution of about 100 and 160 nm, respectively, with an optical contrast C ) 18% is derived. sulfonatophenyl)porphine (TPPS), [24][25][26][27][28] which under strong acidic conditions form extended J-aggregates. Several investigators have pointed out that coplanarity is a prerequisite for the initial dimerization step, together with the presence of negatively charged groups on the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…2−9 Much of this effort has been focused on water-soluble meso-tetra(4-sulfonatophenyl)porphyrin (TPPS). Ribóet al 6 investigated aqueous solutions thereof spectroscopically. In studies performed at various concentrations and pH values, they found evidence for the formation of small J (edge-to-edge) and H (face-to-face) aggregates.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The resulting new zwitterionic species (Figure 1b) form J-aggregates, as is evident from the appearance of new absorption bands in the optical spectra. [21][22][23] Specifically, the monomeric absorption peak at around 434 nm (B or, so-called, Soret band) and peaks in the range of 500-650 nm (Q bands) transform into much narrower red-shifted peaks at 490 and 709 nm, respectively, which has been attributed to the appearance of extended excited states [21][22][23] shared by a number of TPPS 4 monomers.…”
Section: Introductionmentioning
confidence: 99%